KARAKTERISTIK HABITAT POHON KEPEL (Stelechocarpus burahol) DI KAWASAN HUTAN GUNUNG TILU KPH KUNINGAN - Lidia Tamia Anjani; Yayan Hendrayana; Adhya, Ilham (Journal of Forestry and Environment, 2025)
The Kepel tree Stelechocarpus burahol is a rare plant species that has high ecological and cultural value, but its existence is increasingly threatened and difficult to find. This study aims to identify the characteristics of the kepel tree habitat in the Gunung Tilu Forest area, KPH Kuningan, to support conservation and preservation efforts. The research was conducted using exploration methods and the creation of sample plots to analyze biotic factors (companion vegetation) and abiotic factors (soil pH, altitude, temperature, and humidity). The result of the study showed that kepel trees grow well on latosol type soil with neutral pH, temperatures ranging from 25o C (cold category), relative humidity of 70% (rather dry), and on steep slopes of 45-46 o. commonly found companion vegetation is coffee (Coffea sp.), kidahu, and caruy. The hignest importance value index (IVI) at various tree growth stages indicates the dominance of kepel trees in their habitat. This finding provides impormant information for conservation strategies based on the natural habitat of kepel trees.